Manfaat Dan Fungsi Komite Audit Dalam Mewujudkan Tata Pengelolaan Perusahaan Yang Baik (Good Corporate Governance): Persepsi Manajemen Perusahaan Go Public - Indriani, Indriani; Nurkholis, Nurkholis (TEMA, 2002)
Good corporate governance is a management way that aims at im¬proving performance and giving economic value added for the stake¬holders. Basic principles in implementing good corporate gover¬nance include: fairness, responsibility, accountability, and trans¬parency. Audit committee possess very important role in implement¬ing good corporate governance principles. The audit committee help commissioners in applying control into management activities. But, in the case of Indonesia recently, the role and function of audit committee might still be questionable. The purpose of this research is to understand the perception of public companies management towards benefits and function of audit committee. This research examined 5 variables including (1) the level of understanding, (2) qualification of audit committee staff, (3) Junction of audit commit¬tee, (4) benefits for the management and (5) benefits for the com¬pany. This research used Mann Withney U test to examine the difference between 2 groups and Kruskal Wallis test to examine the difference among many groups. The results showed that, in general, threre was no different perception among groups of man¬agement. Different peception towads the role and functions of audit committee was only found between financial related departments (accounting, finance, and internal auditor) and non-finance depart¬ments. Keywords: good corporate governance, audit committee, manage¬ment perception.